Logistics - its role, significance and approaches - Milenkov, Marjan A.; Sokolović, Vlada S.; Milovanović, Vladimir R.; Milić, Marija D. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose:The paper presents the development of logistics as a specific field of military branch, a contemporary field of business and a scientific discipline which inspires many researchers, theorists and practitioners to approach logistical problems from various aspects. The essence of logistics is an integrated approach to all its constituent activities, which reduces costs and increases the efficiency and effectiveness of the logistics system in supporting the primary activities of an organization or a technical system. Due to intensive and multidimensional development of logistics and its applications in various fields, the need for highly educated logistics personnel with specialized knowledge for performing a wide range of activities in the logistics system is becoming increasingly necessary. Methods: Based on the description of military, business, national and humanitarian logistics and a comparative analysis, their mutual relationship is shown. Results: Based on the performed analysis, an explanation of the importance of studying logistics as a multidisciplinary science and pointing out the need for specific training of logistics personnel was given. Conclusion: Logistics is intensively developing in various fields depending on the goals of the system (organizational and technical) it supports. In general, commercial logistics is evolving faster than military logistics, and many innovative commercial logistics solutions are being deployed in military logistics. However, certain solutions that produce good results in the commercial sector do not produce adequate results in the military. Therefore, it is necessary to carry out research and study of the functioning of logistics systems in different fields and carefully integrate individual solutions into the military logistics system. As the most complex logistics system, military logistics requires specific staffing and training of logistics professionals.